2018
DOI: 10.1371/journal.pntd.0006621
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the microtranscriptome of macrophages infected with virulent, attenuated and saprophyte strains of Leptospira spp.

Abstract: Leptospirosis is a bacterial zoonosis, caused by Leptospira spp., that leads to significant morbidity and mortality worldwide. Despite considerable advances, much is yet to be discovered about disease pathogenicity. The influence of epigenetic mechanisms, particularly RNA-mediated post-transcriptional regulation of host immune response has been described following a variety of bacterial infections. The current study examined the microtranscriptome of macrophages J774A.1 following an 8h infection with virulent,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…A recent work that examined the microtranscriptome of murine macrophages J774A.1 stimulated with virulent, attenuated, and saprophyte strains of Leptospira showed differential expression of 29 miRNAs. Of these 29 miRNAs, the highest fold change was observed for miR155-5p in cells stimulated with pathogenic L. interrogans ( 42 ). We did not see an upregulation of this miR155-5p, which could be due to different factors, including but not limited to the difference in the assay method, the cell type, and the culture conditions.…”
Section: Discussionmentioning
confidence: 99%
“…A recent work that examined the microtranscriptome of murine macrophages J774A.1 stimulated with virulent, attenuated, and saprophyte strains of Leptospira showed differential expression of 29 miRNAs. Of these 29 miRNAs, the highest fold change was observed for miR155-5p in cells stimulated with pathogenic L. interrogans ( 42 ). We did not see an upregulation of this miR155-5p, which could be due to different factors, including but not limited to the difference in the assay method, the cell type, and the culture conditions.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study from our group has shown that BCL2 is a potentially down-regulated by mmu-mir-7667-3p following infection with L . interrogans , suggesting that cell survival could be compromissed after macrophages infection by the spirochete [29].…”
Section: Discussionmentioning
confidence: 99%
“…Murine monocyte-macrophage cells ( Mus musculus monocyte-macrophage cell line J774A.1), provided by the Paul Ehrlich cell bank (Rio de Janeiro, Brazil), was used as described [26]. Cells were maintained at 37° C, 5% CO2 in RPMI-1640 media (Sigma, USA) supplemented with 10% heat-inactivated fetal bovine serum (Gibco, USA), 100 ug/mL streptomycin (Sigma Chemical Co St.Louis, MO), 0.03% L-glutamine solution (Sigma) and 100 UI/mL of penicillin, in 6-well cell culture plates (3cm/well) until confluency [22,29].…”
Section: Methodsmentioning
confidence: 99%
“…In fact, Schulte et al [35] concluded that increased TNF-α, IL-1β and IL-6 can activate the coagulation system in endotoxemic models. The high concentration of IL-6 is an indicator of septic shock and correlates with the severity of leptospirosis [36].…”
Section: Discussionmentioning
confidence: 99%